Implementasi Model Pembelajaran PQ4R (Preview, Question, Read, Reflect, Recite And Review) untuk Meningkatkan Pemahamanan Siswa Terkait Materi Pokok Tanah dan Organisme Tanah di Kelas IX-7 MTsN 2 Kota Bima - Siti Nuraini (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2021)
Learning that has been taking place in the classroom has not been able to attract attention so that students seem apathetic towards the material presented by the teacher. Students who actively ask or answer teacher or friend questions are still very low. Soil and Soil Organisms are no exception. To overcome this problem, it is necessary to apply the PQ4R model (Preview, Question, Read, Reflect, Recite and Review). The PQ4R model is a refinement of the PQRST (Preview, Question, Read, State and Test) and SQ3R (Survey, Question, Read, Recite and Review) models. The learning model is a way of studying texts (readings), especially those contained in books, scientific articles and research reports specifically to understand the contents of the text. The PQ4R model can help students to remember what they have read and forbid students to remember what they have read and forbid students about how to learn, how to remember and how to think. After conducting two cycles of classroom action research, it can be concluded that the application of the PQ4R learning model has been able to improve student learning outcomes in cognitive and affective aspects